2001
DOI: 10.1046/j.1523-1755.2001.0590041211.x
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotection: One or many therapies?

Abstract: The term "renoprotection" often evokes a single image:Background. Renal disease that progresses to end-stage reangiotensin-converting enzyme (ACE) inhibition therapy nal disease (ESRD) imposes a great burden on the affected to slow the "progression of renal disease." ACE inhibiindividual and on society, which mainly bears the cost of ESRD tors certainly deserve that reputation [1]. Nevertheless, (currently more than $10 billion to treat about 333,000 patients this therapy alone rarely stops renal disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
1
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 106 publications
(41 reference statements)
0
91
1
7
Order By: Relevance
“…Hyperuricemia is common in patients with renal disease, but it has almost never been considered a risk factor for progression (25). However, two studies have found that hyperuricemia is an independent risk factor for progression in IgA nephropathy (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia is common in patients with renal disease, but it has almost never been considered a risk factor for progression (25). However, two studies have found that hyperuricemia is an independent risk factor for progression in IgA nephropathy (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Quanto maior o grau de proteinúria, mais intensamente a pressão arterial deve ser reduzida 9,10 . Ainda, a utilização de inibidores da enzima conversora e dos antagonistas da angiotensina II tem um efeito protetor renal independente do seu efeito na pressão arterial 9,14,15 .…”
Section: Introductionunclassified
“…Com o número crescente de pacientes em diálise é interessante identificar, entre os hipertensos, quais evoluirão para IRCT, uma vez que, dessa maneira, poder-se-á traçar estratégias de proteção renal para reduzir a frequência dessa complicação 9,16,17 .…”
Section: Introductionunclassified
“…Therefore, the emphasis is very much on early intervention to decelerate the rate of decline once CRF is established. Many factors (5) are now known to influence the progression of renal decline. Some, such as gender, are not open to adjustment, whereas others, including smoking, proteinuria, and hypertension (5,6), may be modified.…”
mentioning
confidence: 99%
“…Many factors (5) are now known to influence the progression of renal decline. Some, such as gender, are not open to adjustment, whereas others, including smoking, proteinuria, and hypertension (5,6), may be modified. Undoubtedly, the best evidence comes from the association between elevated BP and adverse renal outcome in both diabetic (7) and nondiabetic (8,9) patients.…”
mentioning
confidence: 99%